Biological and biochemical diversity in different biotypes of spotted stem borer, Chilo partellus (Swinhoe) in India - Dhillon, Mukesh K. (Sci Rep, 2021)
Because of variation in incidence and severity of damage by Chilo partellus (Swinhoe) in different geographical regions, it is difficult to identify stable sources of resistance against this pest. Therefore, the present studies were undertaken on biological attributes (damage in resistant and susceptible genotypes, survival and development) and biochemical profiles (amino acids and lipophilic compound) of C. partellus populations from eight geographical regions to understand it’s population structure in India. There was a significant variation in biological attributes and biochemical profiles of C. partellus populations from different geographical regions. Based on virulence and biological attributes, similarity index placed the C. partellus populations in five groups. Likewise, lipophilic and amino acid profiling also placed the C. partellus populations in five groups. However, the different clusters based on biological and biochemical attributes did not include populations from the same regions. Similarity index based on virulence, biological attributes, and amino acids and lipophilic profiles placed the C. partellus populations in six groups. The C. partellus populations from Hisar, Hyderabad, Parbhani and Coimbatore were distinct from each other, indicating that there are four biotypes of C. partellus in India. The results suggested that sorghum and maize genotypes need to be tested against these four populations to identify stable sources of resistance. However, there is a need for further studies to establish the restriction in gene flow through molecular approaches across geographical regions to establish the distinctiveness of different biotypes of C. partellus in India.